2023
DOI: 10.1101/2023.02.27.530199
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Unistrand piRNA clusters are an evolutionarily conserved mechanism to suppress endogenous retroviruses across theDrosophilagenus

Abstract: The PIWI-interacting RNA (piRNA) pathway plays a crucial role in preventing endogenous genomic parasites, transposable elements (TEs), from damaging the genetic material of animal gonadal cells. Specific regions in the genome, called piRNA clusters, define each species' piRNA repertoire and therefore its capacity to recognize and silence transposons. In the somatic cells of the Drosophila melanogaster ovary, the flamenco (flam) unistrand cluster is the main source of piRNAs and primarily regulates Gypsy family… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 90 publications
(118 reference statements)
2
11
0
Order By: Relevance
“…S2A), arguing against a non-canonical, env-independent soma-to-germline transmission process. These data are consistent with the absence of an anti-copia defense program by the host piRNA pathway in follicle cells that efficiently silences the expression of Errantiviruses [45][46][47]: piRNAs targeting copia in somatic ovarian cells are approximately 10-to 100-fold lower than those targeting the different Errantiviruses (Fig. 5A).…”
Section: Copia Is Differentially Repressed In Somatic Cells and The G...supporting
confidence: 84%
“…S2A), arguing against a non-canonical, env-independent soma-to-germline transmission process. These data are consistent with the absence of an anti-copia defense program by the host piRNA pathway in follicle cells that efficiently silences the expression of Errantiviruses [45][46][47]: piRNAs targeting copia in somatic ovarian cells are approximately 10-to 100-fold lower than those targeting the different Errantiviruses (Fig. 5A).…”
Section: Copia Is Differentially Repressed In Somatic Cells and The G...supporting
confidence: 84%
“…5a). We compared our CUT&RUN data for H3K9me3 and H3K27me3 marks with small RNA-seq of ovaries from these species (Lopik et al 2023). We divided the genomes into 10kb bins that were then classified onto 15 groups according to piRNA levels present in each species.…”
Section: Kipf-independent Rhi Binding Depends On E(z)mentioning
confidence: 99%
“…Each genomic bin was assigned one of three possible states: none (0), flam-like cluster (1), and centromere-like region (2). As ground truth we used previously reported cluster coordinates (van Lopik et al, 2023). Centromeric regions were defined at chr2 and chr3 as described in Supplementary Methods S1.…”
Section: Hidden Markov Model Statesmentioning
confidence: 99%
“…For a long time, flam -syntenic clusters were identified only in species closely related to D. melanogaster (Chirn et al ., 2015; Malone et al ., 2009). We recently reported that flam is evolutionarily conserved beyond the melanogaster subgroup and that flam -like loci exist in species that diverged from D. melanogaster at least 33 million years ago (van Lopik et al ., 2023). This raises the possibility that unistrand piRNA clusters may control Gypsy -family TEs across the whole Drosophila genus.…”
Section: Introductionmentioning
confidence: 99%